Ocular manifestations in Herpes Zoster Ophthalmicus - Puri, LR; Shrestha, GB; Shah, DN; Chaudhary, M; Thakar, A (Nepalese Journal of Ophthalmology, 2011)
Background: Ocular complications of herpes zoster ophthalmicus (HZO) may lead to substantial visual disability, severe post-herpetic neuralgia and rarely fatal cerebral complications. Aim: To identify the pattern of ocular manifestation in herpes zoster ophthalmicus. Materials and methods: A cross-sectional descriptive study was under taken including the clinically diagnosed cases of HZO. All of them underwent a complete ophthalmological evaluation. Results: Sixty-eight cases of HZO were examined, of which 37 (54.4 %) were male and 31 (45.6%) female. The mean age was 48.7 ± 18.5 years. Most of the patients (64.7 %) were above the age of 40 years. 77.94 % of the patients had some form of ocular involvement. Pain (77.9 %) was the commonest ocular complaint. In young patients less than 35 years, HIV was the most common risk factor (19.3 %).Visual status was good in the majority (73.5 %) of patients at presentation. Lid and adnexal findings (45.8 %) were most common ocular involvement followed by conjunctivitis (41.1 %). Corneal complication was seen in 38.2 % of cases, uveitis in 19.1 % and post-herpetic neuralgia (PHN) and secondary glaucoma each in 5.8 %. Conclusion: Eyelid and ocular adnexal involvement is most commonly found in patients with herpes zoster ophthalmicus followed by corneal complication and uveitis. There needs to be awareness of ocular involvement, which can be sight threatening, among the HZO patients and other medical departments and an increased emphasis on regular ophthalmic examination. Key words: herpes virus, herpes zoster, conjunctivitis, keratitis DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5271 Nepal J Ophthalmol 2011; 3(2): 165-171